Advances in targeting the vacuolar proton-translocating ATPase (V-ATPase) for anti-fungal therapy - Hayek, Summer R.; Lee, Samuel A.; Parra, Karlett J. (Frontiers in Pharmacology, 2014)
Vacuolar proton-translocating ATPase (V-ATPase) is a membrane-bound, multi-subunit enzyme that uses the energy of ATP hydrolysis to pump protons across membranes. V-ATPase activity is critical for pH homeostasis and organelle acidification as well as for generation of the membrane potential that drives secondary transporters and cellular metabolism. V-ATPase is highly conserved across species and is best characterized in the model fungus Saccharomyces cerevisiae (S. cerevisiae). However, recent studies in mammals have identified significant alterations from fungi, particularly in the isoform composition of the 14 subunits and in the regulation of complex disassembly. These differences could be exploited for selectivity between fungi and humans and highlight the potential for V-ATPase as an anti-fungal drug target. Candida albicans (C. albicans) is a major human fungal pathogen and causes fatality in 35% of systemic infections, even with anti-fungal treatment. The pathogenicity of C. albicans correlates with environmental, vacuolar, and cytoplasmic pH regulation, and V-ATPase appears to play a fundamental role in each of these processes. Genetic loss of V-ATPase in pathogenic fungi leads to defective virulence, and a comprehensive picture of the mechanisms involved is emerging. Recent studies have explored the practical utility of V-ATPase as an anti-fungal drug target in C. albicans, including pharmacological inhibition, azole therapy, and targeting of downstream pathways. This overview will discuss these studies as well as hypothetical ways to target V-ATPase and novel high-throughput methods for use in future drug discovery screens.